Hygiene, balanced diet and physical exercise in Basic Education: The importance of the playful approach - S. Silva, Danielle; S. Campos, Iasmin; L. S. Avelar, Mariana; R. Pinheiro, Náthale; Aziz, Fernanda; Barbizan Petinari, Roberta (Guará Journal, 2022)
The number of metabolic disorders has increased substantially in recent decades due to changes in society’s lifestyle habits, which are based on a sedentary daily life and are associated with the intake of hypercaloric foods and low nutritional value. The earlier these harmful habits are observed, the more wor-rying are the consequences. Therefore, with the aim of preventing these diseases starting with lower age groups, health education was carried out with children from 8 to 10 years of age, during biweekly visits to the Honorinda Ferreira Cardoso Municipal School, in which activities were developed educatio-nal games addressing healthy living habits. From these activi-ties, themes about the importance of physical activity; personal hygiene; selection of food in meals; healthy and economically accessible recipes were developed and discussed. To measure results, the parents of these students were questioned about possible changes in the habits of these children. It can be observed that the objectives of play activities were achieved, since was observed children are more critical regarding food con-sumption and personal hygiene and more willing to practice physical activities, besides multiplying this knowledge, leading to their family nucleus. Key words: Health education, playful, child, elementary school.